2016
DOI: 10.1186/s13099-016-0098-0
|View full text |Cite|
|
Sign up to set email alerts
|

The Salmonella pathogenicity island 13 contributes to pathogenesis in streptomycin pre-treated mice but not in day-old chickens

Abstract: BackgroundSalmonella enterica serovar Enteritidis (S. Enteritidis) is a human and animal pathogen that causes gastroenteritis characterized by inflammatory diarrhea and occasionally an invasive systemic infection. Salmonella pathogenicity islands (SPIs) are horizontally acquired genomic segments known to contribute to Salmonella pathogenesis. The objective of the current study was to determine the contribution of SPI-13 to S. Enteritidis pathogenesis.MethodsWe deleted the entire SPI-13 (∆SPI-13) from the genom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 34 publications
1
24
0
Order By: Relevance
“…However, in that work, Espinoza et al discovered that SPI-13 does play a role in Salmonella internalization into mouse – but not human – macrophage (23). Combined with previous works showing reduced survival of IRO mutants in mice, this operon may play a more significant survival role in the context of an animal infection (19–22).…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…However, in that work, Espinoza et al discovered that SPI-13 does play a role in Salmonella internalization into mouse – but not human – macrophage (23). Combined with previous works showing reduced survival of IRO mutants in mice, this operon may play a more significant survival role in the context of an animal infection (19–22).…”
Section: Discussionsupporting
confidence: 55%
“…Interestingly, the IRO genes of Salmonella have been shown to be induced heavily in macrophage but not under any other condition tested, supporting a role in degrading macrophage-produced itaconate (17–19). High throughput screens have suggested that genes from this operon are important for Salmonella survival in mice (2022). Furthermore, it has also been shown that SPI-13 is present in generalist but not human-restricted serovars of Salmonella , possibly due to reduced itaconate synthesis in human cells (23).…”
Section: Introductionmentioning
confidence: 99%
“…Fluorescent Salmonella Enteritidis enables SPI-1 quantitation in the intestines of chicks. Having determined that our fluorescent proteins did not interfere with virulence, we moved these constructs into S. Enteritidis strain CDC_2010K_0968, a clinical isolate associated with the 2010 egg outbreak of Salmonella infection in the United States (28,29). The strain behaved as expected in vitro (see Fig.…”
Section: Resultsmentioning
confidence: 91%
“…An isogenic ΔphoN::kan mutant was also constructed and used as the wild-type strain in mouse competition. Salmonella Enteritidis strain MD15 (a gift from Devendra Shah [28,29]) was the background for all strain variants employed in chicken studies. To generate a nalidixic acid-resistant isolate, 100 l of a log-phase culture was plated on LB agar containing 100 g/ml nalidixic acid.…”
Section: Methodsmentioning
confidence: 99%
“…SPI-2 to SPI-4 are necessary for bacterial survival and proliferation inside host cells, and SPI-5 seems to be involved in inflammation and chloride secretion [32]. SPI-13 and SPI-14 are known to be able to promote colonization of Salmonella in the host intestine [33,34]. The presence of SPIs in ST1120 was explored by using the newly developed Web tool SPIFinder 1.0.…”
Section: Pathogenesis and Virulence Factorsmentioning
confidence: 99%